Current approaches for modeling ecosystem services and biodiversity in agroforestry systems: Challenges and ways forward - Rahman, Muhammed Habib ur; Ahrends, Hella Ellen; Raza, Ahsan; Gaiser, Thomas (Frontiers in Forests and Global Change, 2023)
Limited modeling studies are available for the dynamics-based simulation of ecosystem services (ESS) and biodiversity (BD) in agroforestry systems (AFS). To date, limited field scale AF models are available to simulate all possible ESS and BD together. We conducted an extensive systematic review of available AF, BD, and soil erosion models for simulation potential for seven more desirable ESS. Simple to complex AF models has an inherent limitation of being objective-specific. Although a few complex and dynamic AF models also did not meet recent interests and demands. Further, many ESS modules especially soil erosion, GHGs emission, groundwater recharge, onsite water retention, nutrients leaching, and BD are often missing in AF models. While physical to process-based soil erosion models can be used in combination with AF models. Likewise mechanistic and process-based BD diversity models lacking and limited used for ESS under AFS. However, further model development or integration and coupling are needed for better dynamic prediction considering all basic complex interactions for the simulation of ESS and BD altogether. There are different possibilities but a proficient modeling approach for better reliability, flexibility, and durability is to integrate and couple into a process-based dynamic modular structure. We further suggest that crop modeling frameworks like SIMPLACE and APSIM could be potential ones for the integration and coupling of different suitable modeling approaches (AF, soil protection, GHGs emission, flood prevention, carbon sequestration, onsite water retention, ground recharge, nutrient leaching, and BD modules) in one platform for dynamic process based ESS estimation on daily basis at the field scale.